World Development Indicators 2008 : Poverty Data - World Bank (Washington, DC, 2017)
This supplement to World Development Indicators 2008 provides estimates of global poverty that are the first re-evaluation of the World Bank's "$1 a day" poverty line since 1999. The international poverty line has been recalibrated at $1.25 a day, using new data on purchasing power parities (PPPs), compiled by the International Comparison Program, and an expanded set of household income and expenditure surveys. New measurements of the extent and depth of poverty are presented here for 115 developing countries, along with poverty measurements based on their national poverty lines. The new data change our view of poverty in the world. There are more poor people, extremely poor people, and the incidence of poverty reaches farther into middle-income countries. Previous rounds of the International Comparison Program underestimated average price levels in developing countries (perhaps by not fully adjusting for quality differences) and thus overestimated standards of living. By the new measurements 1.4 billion people are living in extreme poverty, more than one-quarter of the population of developing countries. But countries and regions that have reduced their poverty rates are no less successful by the new measurements. In 1990, at the beginning of the period tracked by the Millennium Development Goals, 42 percent of the people in developing countries lived on less than $1.25 a day. Over 15 years global poverty fell by an average of 1 percentage point a year. At that rate the target set by the Millennium Development Goals will be surpassed at the global level and in East Asia, where poverty rates have fallen fastest, by 2015. But large differences remain between regions, across countries in the same region, and even within countries. The data presented here allow us to see where some of those differences occur and point the way toward a world free from the most extreme poverty.